(untitled) (Veterinary Science, 2017)
Eisenmenger Syndrome is a set of symptoms that occur as a result of the presence of blood shunt “from right to left” caused by pulmonary hypertension secondary to increased pulmonary vascular resistance. As postulated Nelson and Couto (2005), the presentation of this syndrome usually happens until the individual reaches six months of life. This work describes the presentation of Eisenmenger Syndrome in a canine patient, poodle, male, 4-year-old, who arrived in consultation with a very marked dyspnea and cyanosis in all its explorable mucosae. A complete clinical examination was performed, and then thorax radiography, two-dimensional echocardiography, M-mode echocardiography, doppler echocardiography and electrocardiogram were carried out